An instrumental case study of marital happiness among persons with visual disability in Malaysia - Teoh, Jia Long; Muhammad Idris Bullare @ Bahari (Georgian Technical University, 2022)
This study explores marital happiness among Persons with Visual Disabilities (PwVD) in Malaysia. This research has utilized the instrumental case study design. Most investigations regarding marriage or parenting among PwVD have only focused on parenting experiences and adaptations. A total of 10 PwVD who are married were recruited using maximal purposeful sampling, which is supplemented by the snowballing strategy in this study. Qualitative content analysis has been applied as a method of data analysis. The researcher has also utilized member checking and investigator triangulation as validation strategies. Generally, three themes regarding the dimensions of marital happiness have been constructed—for example, positive emotion, positive relationship, and meaning. However, in this study, 11 themes were found in sources of marital happiness. All themes are positively discussed in this finding study.